2008
DOI: 10.1534/genetics.107.081869
|View full text |Cite
|
Sign up to set email alerts
|

A Gain-of-Function Suppressor Screen for Genes Involved in Dorsal–Ventral Boundary Formation in the Drosophila Wing

Abstract: The Drosophila wing primordium is subdivided into a dorsal (D) and a ventral (V) compartment by the activity of the LIM-homeodomain protein Apterous in D cells. Cell interactions between D and V cells induce the activation of Notch at the DV boundary. Notch is required for the maintenance of the compartment boundary and the growth of the wing primordium. Beadex, a gain-of-function allele of dLMO, results in increased levels of dLMO protein, which interferes with the activity of Apterous and results in defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 87 publications
2
32
1
1
Order By: Relevance
“…Indeed, miR-282, 26% of whose embryonic expression is driven by isomiR-As, has been genetically linked to dorso-ventral boundary establishment in Drosophila embryos (Bejarano et al 2008). Indeed, stabilization of miRNAs by adenylation has been previously shown in black cottonwood (Lu et al 2009) and mouse (Katoh et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, miR-282, 26% of whose embryonic expression is driven by isomiR-As, has been genetically linked to dorso-ventral boundary establishment in Drosophila embryos (Bejarano et al 2008). Indeed, stabilization of miRNAs by adenylation has been previously shown in black cottonwood (Lu et al 2009) and mouse (Katoh et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although mir-282 and mir-275 lack thorough functional evidence, several EP insertions at the mir-282 locus were identified in screens for wing development and circadian rhythm (Molnar et al 2006;Bejarano et al 2008;Dubruille et al 2009) while the presumptive core promoter of pri-mir-275 maps exactly to the cuckold mutation (chr2L: 7,423,896-7,423,995) (Castrillon et al 1993), strongly suggesting that the observed behavioral defect for cuc 1 is caused by a deregulation of the pri-mir-275 transcript. In Drosophila, <50% of all miRNA loci overlap with protein-coding transcripts with the majority remaining as intergenic.…”
Section: Prc1 Binds Promoters Of Coding and Noncoding Genesmentioning
confidence: 99%
“…The latter notion is further supported by our findings that the mir-282 gene is active at the pupal stage and it is conserved in holometabolic insects, which undergo complete metamorphosis. Moreover, in genetic interaction screens, mir-282 overexpression was found to have effect on pupal wing development and nervous system function (Bejarano et al 2008;Cao et al 2008).…”
Section: Discussionmentioning
confidence: 99%